Effect of milrinone versus placebo on hemodynamic in patients with septic shock: A randomize control trial - Chobngam, Suratee; Tongyoo , Surat (Clinical Critical Care, 2022)
Background: Sepsis is one of the most serious healthcare problems worldwide, which is associated with high mortality and financial burdens. The common causes of death are refractory shock and multi-organ failure. Myocardial dysfunction, a relatively common complication of septic shock, causes a significantly decrease in stroke volume and cardiac output. This results in insufficient blood supply to the organs, creates multi-organ failure and finally, leading to death. The Surviving Sepsis Campaign Guidelines 2016 also recommended using dobutamine in septic shock patients who had been resuscitated until achieving normal blood pressure target of mean arterial pressure 65 mmHg or more, but still had evidence of inadequate tissue perfusion. Milrinone action via an alternative pathway from the sympathetic inotropic agents, makes the milrinone to be used as an option for improve cardiac function among sepsis patients. However, there are few studies of milrinone in patients with septic shock. Methods: We plan to conduct a double blind randomized controlled trial, enrolling patients at Siriraj hospital and Hat-Yai hospital. The adults with the diagnosis of septic shock according to definition of SEPSIS III will be screened. Patients who receive fluid resuscitation at least 30 mL/kg, mean arterial pressure (MAP) ≥ 65 mmHg, with a clinical sign of poor tissue perfusion, or evidence of impaired left ventricular systolic function (left ventricular ejection fraction (LVEF) < 40%) will be enrolled. The patients were randomly assigned in a 1:1 ratio by their sequential number to receive either milrinone (intervention group) or placebo (control group). The physician performs an echocardiogram for assessing cardiac function, before the starting of the study drug and after the 6 and 24 hours. The monitoring of vital signs, urine output, and lactate at 6 and 24 hours after milrinone or placebo commencement is recorded. Conclusion: This study will evaluate the efficacy of milrinone in improving cardiac output among adult patients with septic shock who is resuscitated to achieve target blood pressure but still have signs of poor tissue perfusion.